Musikalsk symbolisme: En indkredsning af symbolismen og en særlig musikalsk symbolisme inden for ‘det moderne’ - Tange, Esben (Danish Yearbook of Musicology, 2002)
Starting from an understanding of symbolism as a historically situated approach to reality, which evolves from an experience of God’s absence, the article characterizes the symbolistic works of art. These are of a metaphysical nature and characterized by perceivable symbols, which finds expression in atmospheres (‘Stemninger’). At the same time distinct physical appearances in the works are cultivated, which are summarized in the idea of ‘the thing’. Using Rued Langgaards The Music of the Spheres (1916-18) as a case in point, a specific symbolism of music is outlined within the concept of ‘die musikalische Moderne’ (Dahlhaus). Symbolistic works are characterized by violation of the traditional logic of musical development. They are composed of larger elements, which in and between themselves are exposed to permutation, leading to transformation and the juxtaposition of essentially different stylistic modes of expression. From that, and in interaction with extramusical factors, another kind of logic and semantics can arise in symbolistic musical works.